SENTRA KERAJINAN KULIT DI KEMANG - Anita Darmawan; Timmy Setiawan (Jurusan Arsitektur dan Perencanaan, 2019)
Handcraft is one of three sub-sectors whose contribute significantly to the development of creative economic industry growth. The most creative industry figure are from the millennial generation. Handcraft art is one of the sub-sectors that is represents the characteristic of the Indonesian nation. Leather craft is one of the raw materials for craft arts that is greatly demand by millennials. In the present, Indonesian leather crafts are increasingly diverse. But the problem of developing a creative economy and startup is capital needs. The problem causes startups to not be able to develop optimally. This project is a forum for creative craftsmen by combining informal educational facilities and exhibition halls. This activity is intended to support each other so that leather craftsmen can immediately showcase their work and can be directly seen and bought by consumers. Consumers can simultaneously see the process and learn how to make it. The project is located in Kemang which is known internationally as a creative industrial area where many millennial generations gather. And the potential for infrastructure development. With this project in addition to bringing financial benefits from the work of ideas and innovation made from leather-based products, it is also expected to build and generate millennial generations, as the main actors, to form communities that aim to gather and share experiences and insights about their love of leather crafts. This activity makes the millennial generation active and creative to socialize in the wider community through leather crafting. In addition, this project was created to increase the appreciation of the community, both those who are interested in their fields and lay people who come to the value of leather-based products by observing the process of making their products.Abstrak Kerajinan (kriya) adalah salah satu dari tiga subsektor yang kontribusinya cukup signifikan dalam perkembangan industri ekonomi kreatif dan pelaku industri kreatif paling banyak dari generasi milenial. Seni kriya merupakan salah satu sub sektor yang menjadi ciri khas Bangsa Indonesia. Kerajinan kulit merupakan salah satu bahan baku material seni kriya yang banyak diminati kalangan milenial. Kerajinan kulit Indonesia di era kekinian semakin beragam. Namun persoalan dari pengembangan ekonomi kreatif dan startup adalah kebutuhan modal dan pemasaran. Adanya kendala tersebut menyebabkan startup tidak dapat berkembang maksimal. Proyek ini merupakan wadah untuk pengerajin kulit berkreasi dengan menggabungkan sarana pendidikan informal dan ruang pameran. Kegiatan ini dimaksudkan untuk saling mendukung sehingga pengerajin kulit dapat langsung memamerkan hasil karyanya dan dapat langsung dilihat dan dibeli oleh konsumen. Konsumen juga sekaligus dapat melihat proses pengerjaannya dan belajar membuat. Proyek berada di Kemang yang dikenal secara internasional sebagai kawasan industri kreatif dimana banyak generasi milenial berkumpul. Serta berpotensi dalam perkembangan infrastrukturnya. Dengan adanya proyek ini selain mendatangkan keuntungan finansial dari karya ide dan inovasi produk berbahan dasar kulit, juga diharapkan membangun dan membangkitkan generasi milenial, selaku pelaku utama, untuk membentuk komunitas yang memiliki tujuan untuk berkumpul serta berbagi pengalaman dan wawasan mengenai kecintaan mereka tentang kerajinan kulit. Kegiatan ini menjadikan generasi milenial aktif dan kreatif untuk bersosialisasi dalam kalangan masyarakat luas melalui kerajinan kulit. Selain itu proyek ini dibuat untuk meningkatkan apresiasi masyarakat baik yang tertarik dibidangnya maupun orang awam yang datang terhadap nilai produk-produk berbahan dasar kulit dengan mengamati proses pembuatan produknya.